Efficacy analysis of microinvasive glaucoma surgery alone or in combination with phacoemulsification in patients with normal tension glaucoma: a systematic review and meta-analysis - Zhen Yu; Mengfan Wu; YuFei Tao; Zihan Huang; Mingmin Yang; Xiaohua Pan; Dimitrios Ntentakis; Ning Fan (BMC Ophthalmology)
Abstract Objective To assess the effectiveness of minimally invasive glaucoma surgery (MIGS) as monotherapy, or in combination with phacoemulsification, in the management of normal tension glaucoma (NTG). Methods A systematic literature review and meta-analysis were conducted. The literature search was performed using four electronic databases, including Pubmed, Embase, Web of science, and Cochrane Central Register of Controlled Trials, to identify studies evaluating the efficacy of MIGS on patients with NTG, published from October 1, 2019 to October 1, 2024. The articles meeting our inclusion criteria were independently screened and assessed by three reviewers. Effect estimates associated with NTG were pooled and evaluated via meta-analysis. The articles retrieved from the databases were systematically analyzed using Citespace 6.2.R3. Results A total of 11 English-language studies involving 413 eyes from 327 NTG patients were included. Follow-up ranged from 6 to 60 months. MIGS alone reduced IOP by 2.62 mmHg (95% CI: -3.70 to -1.54; Z = 4.77, P < 0.00001), while MIGS with cataract surgery reduced IOP by 2.09 mmHg (95% CI: -2.83 to -1.35; Z = 5.53, P < 0.00001). The number of IOP-lowering medications decreased by 1.47 with MIGS alone (95% CI: -2.16 to -0.77; Z = 4.07, P < 0.0001) and by 1.13 with combined surgery (95% CI: -1.75 to -0.52; Z = 3.63, P = 0.0003). No significant differences were observed between the two surgical approaches. Conclusion The meta-analysis demonstrated that either MIGS alone or combined with phacoemulsification effectively reduced the IOP and the requirement for IOP-lowering medications in NTG patients. MIGS alone or combined with phacoemulsification reduced the IOP most at 12 months, and the lowest IOP-lowering medications at 24 months in postoperative patients with NTG.